2014
DOI: 10.1007/s11552-014-9671-5
|View full text |Cite
|
Sign up to set email alerts
|

Composite Grafting for Pediatric Fingertip Injuries

Abstract: Background Fingertip injuries are common in the pediatric population. Composite grafting is a frequently used technique for distal amputations in children given the reported success rate. We sought to study the early clinical results of composite grafting for fingertip injuries in the pediatric population. Methods A retrospective review was performed over a 5-year period at a tertiary care pediatric hospital to identify those patients who underwent composite grafting of fingertip injuries. Patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Due to time elapsed in the work-up to surgical intervention, 75% of patients were operated on after 6 hours. Although only a small group of patients were operated on directly and before 6 hours, no difference in outcomes between transfer patients and direct admissions was found in this study, replicating findings by Eberlin et al 25 On the other hand, Moiemen and Elliot 5 found that amputations repaired as composite grafts more than 5 hours after amputation were less likely to survive. This 5-hour cutoff point; however, was later criticized for being arbitrary and not the classic 6-hour “ischemic” time and not identified as independent predictor of graft success in logistic regression, 25 with 2 subsequent larger case series failing to replicate the findings.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Due to time elapsed in the work-up to surgical intervention, 75% of patients were operated on after 6 hours. Although only a small group of patients were operated on directly and before 6 hours, no difference in outcomes between transfer patients and direct admissions was found in this study, replicating findings by Eberlin et al 25 On the other hand, Moiemen and Elliot 5 found that amputations repaired as composite grafts more than 5 hours after amputation were less likely to survive. This 5-hour cutoff point; however, was later criticized for being arbitrary and not the classic 6-hour “ischemic” time and not identified as independent predictor of graft success in logistic regression, 25 with 2 subsequent larger case series failing to replicate the findings.…”
Section: Discussionsupporting
confidence: 87%
“…Although only a small group of patients were operated on directly and before 6 hours, no difference in outcomes between transfer patients and direct admissions was found in this study, replicating findings by Eberlin et al 25 On the other hand, Moiemen and Elliot 5 found that amputations repaired as composite grafts more than 5 hours after amputation were less likely to survive. This 5-hour cutoff point; however, was later criticized for being arbitrary and not the classic 6-hour “ischemic” time and not identified as independent predictor of graft success in logistic regression, 25 with 2 subsequent larger case series failing to replicate the findings. 7 , 8 Due to the retrospective nature of this study, it was difficult to assess the actions taken in the interim period before surgery; however, it has been noted that quick replacement of the fingertip immediately after injury could contribute to improved graft survival.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Survival rate for the composite graft has been reported to be approximately 50% or less (varying depending on avulsion level or extent), and the size not exceeding 1 cm has been recommended. Thus, when treatment with the composite graft is selected, the treatment plan needs to be devised, taking into consideration prolongation of the duration of injury, possible need for additional surgery upon appearance of partial necrosis, and possible loss of avulsed finger skin [2,3]. For fingertip reconstruction with a local flap, the homodigital dorsal skin flap, reverse digital artery flap, and thenar flap are generally used.…”
Section: Discussionmentioning
confidence: 99%